Determinants of Labor Absorption in Micro, Small, and Medium Enterprises (MSMEs) in Jambi City - Muhammad Zhahran Shiddik; Heriberta; Hardiani (Takaza Innovatix Labs Ltd., 2026)
Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector, play a vital role in labor absorption amid Indonesia's economic challenges, yet factors influencing this remain underexplored in Jambi City. This study aims to analyze the effects of capital access, education level, business duration, and technology utilization on labor absorption in culinary MSMEs there. It employs a quantitative survey method on a population of 14,583 registered culinary MSME actors, yielding 154 respondents via Slovin formula (5% error margin) and purposive sampling. Data from questionnaires were analyzed using SPSS 27 for classical assumption tests and multiple linear regression. Results reveal that all variables simultaneously affect labor absorption significantly (F=51.811, p=0.001; R²=0.582), but partially, only education level (t=2.140, p=0.034) and technology utilization (t=-14.348, p=0.001) show significant effects. Capital Access, Business Duration, Education Level, Labor Absorption, Technology Utilization